THE MYTH OF THE AMERICAN DREAM BETWEEN THE ILLUSION OF HEROISM AND THE CORRUPTION OF POWER IN THE DESIGN OF THE MOVIE POSTER (RAMBO) AS A MODEL - Assist. Prof. Dr. Ahmed Obaid Kadhim Al-Ghazali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The myth occupies an important place in the heritage of humanity. No society or civilization is free of myths associated with its heritage and culture. The heroes of the myth are men of great bone, who have exceptional qualities in terms of the ability to explain the causes and origins of natural, social, and cultural phenomena. As thought evolved, the myth rose to symbolism as an organized social consciousness, explaining in the language of symbols a bunch of ideas that reflect the philosophy of its time and the national spirit of its historical series of novels, expressed through myth as guarding society against its enemies and achieving its desires and aspirations, and capable of finding growing excuses for conflict. Here, the American dream is rooted in the soil of mythology, as a cultural force for keeping America unable to solve its problems, as a constant and unchangeable emblem. These myths have been at the center of Hollywood’s groundbreaking cinematic discourse in American interaction with the world, a speech that vindicates claims of difference, exclusion, and condescension and does not justify flaws, errors, and drowning in the sea of delusions, produced for economic and commercial motives and marketed within an aesthetic character that lures consumers by seducing him into the myths of delusion and the digital seduction of a dysfunctional and troubled cultural reality that is a domestic and global nightmare. Here’s the question: Has American cinematic discourse contributed to the reality of the American dream in Rambo, in its material and idealistic aspect and promoting a culture of violence? The research is based on the pursuit of the American dream in the mythology of cultural Hollywood cinematic discourse, while the aim is to uncover the myths of the American dream and justify the ideological rhetoric of an American identity that elevates the American man to establish dependence, obedience, and hegemony. The result of the search came from the thriller and suspense film (Rambo) colonizing the imagination and future of all other cultures.